A Study on the Diagnostic Effect of Social Media on Libyan EFL University Students Writing Skills in General and Day-to-day Written Communication Specifically - Almushwat, Ruya Faisal; Sabkha, Sarab Assem (International Journal of Linguistics, 2023)
The present study aims to scrutinise the diagnostic effect of social media on Libyan EFL University Students Writing skills in General and day-to-day Written Communication specifically. As social media is a growing phenomenon that contributes to language change and the way we use it, the effects this language change has on EFL students is of particular interest. This research covers Facebook and Instagram, as it also employs a quantitative method with an online questionnaire as its research instrumentation to collect the data. The questionnaire was distributed online through Google forms using a closed-ended questionnaire. The findings indicated that Libyan EFL University Students believe that social media has a positive effect on their language. It was also found that writing is the most affected and improved skill when using social media for learning the English language. Results also indicated that social media helps learners acquire and practise new vocabulary and decrease spelling errors. The researchers recommended more research to assess the influence of other social media platforms on EFL learners, such as Twitter, LinkedIn, and YouTube. Furthermore, further research into the impact of social media on each skill independently is also advised.